Messages about the family in the press and media: A survey in Vietnam - Nguyet, Nguyen Anh (Linguistics and Culture Review, 2022)
Family is the most solid fulcrum and incomparable peace for every human being. It is always a place full of love to return to, so the message of marriage and family is mentioned often in the media in many different ways. This study explores which topics about marriage-family are mentioned the most, how male and female images appear in the family, specifically: the role in maintaining family happiness is assigned. Who are the perpetrators and causes of domestic violence, and how is the gender division of labor in the family reflected in the media? Through research to overcome and gradually eliminate gender stereotypes in media messages, contribute to promoting gender equality.